Students’ Perceptions of Higher Education Assessment Practices in the Context of Artificial Intelligence in Ghana - Owusu Tabiri, Michael; Gyabaah, Opoku; Jones-Mensah, Ivy; Calys-Tagos, Patience (Journal of educational technology development and exchange, 2025)
This study aims to investigate the experiences of university students on the use of artificial intelligence (AI) for assessment in higher education in Ghana. A quantitative survey approach was employed, using an online questionnaire administered to target participants across five public universities. The findings from a final sample size of 509 indicate varying levels of exposure to AI-based tools for assessment, learning, and research. It was found that the majority of the respondents have occasionally (n=218, 42.8%) been assessed using AI-based tools, while very few have very often (n=35, 6.9%) used AI-based tools for assessment as students. It was also revealed in the study that most of the respondents used ChatGPT (n=380, 74.7%) for learning, research, and assignments. Also, AI-supported feedback systems (n=173, 34%) are the most widely used AI-based assessment method by students. Regarding pragmatic approaches to assessment in the era of AI, participants expressed general agreement towards skill-based assessments, provision of continuous feedback, integration of innovative methods, and the use of presentations, practical and application questions for written examinations, although opinions on the replacement of traditional assessments with oral presentations were more divided. These findings underscore the evolving role of AI in higher education and provide insights for educators as well as policymakers seeking to optimize assessment strategies in the era of AI. Further research is recommended to delve into the AI-based assessment methods versus traditional assessment methods in higher education.